Effectiveness of Project Based Learning and Guided Inquiry to Improve Learning Achievement and Entrepreneurship in Blora, Indonesia - Hayuningtyas, Ninditya Enggawati; Suminar, Tri; Suharini, Erni (Journal of Primary Education)
Current education does not always deal with remembering and memorizing but it should be creative and innovative. This research aimed to compare the effectiveness between Project Based Learning (PjBL) and Guided Inquiry (GI) in improving learning achievement and entrepreneurship of fifth graders at primary school. This quantitative research used quasi experimental design. The experimental group was intervened by Project Based Learning while the control group by Guided Inquiry. The population of this research consisted of Gatot Subroto primary school cluster, Blora Municipal. The sample consisted of SDN 1 Kalen and SDN 2 Nglandeyan. From both schools, all fifth graders were taken by using saturated sampling. The techniques of collecting idea were test, questionnaire, observation, interview, and documentation. The hypothesis test used N-Gain and Independent Sample Test analysis. The findings showed that there were differences by using PjBL and GI in improving learning achievement with score of tvalue = 0.980 with sig score 0.000. In improving entrepreneurship, the tvalue = 0.397 with sig score 0.000. Thus, it could be concluded that Project Based Learning was more effective to improve learning achievement and entrepreneurship of the students than Guided Inquiry. It is suggested for the educators to be more creative in using appropriate learning model to the characteristics of the students and school should facilitate teacher to be more innovative.